Sonographic evaluation of spleen size in apparently healthy children in north-west Ethiopia, 2020: time to define splenomegaly - Binalfew Tsehay; Dessalegn Shitie; Abebe Afenigus; Mustofa Essa (BMC, 2021)
Abstract Background Assessment of spleen size is an important part of the clinical skills of medical students and physicians. Many diseases can affect the size of the aforementioned organ, ranging from infective processes to malignant disorders. However, to detect changes, prior knowledge of the actual normal size of these viscera is required in the population being studied. Establishing a customized chart and curve for a specific population of the same sociodemographic characteristics enables a better interpretation of sonographic assessments. Methods A hospital-based cross-sectional study design was conducted among 403 children in primary and referral hospitals of the east and west Gojjam zone. Data were collected using a structured questionnaire, physical examination, and ultrasound. The collected data were entered into Epi Data version 3.1 and exports to SPSS version 24 for analysis. Descriptive data were analyzed using descriptive statistics. A Pearson product-moment correlation was run to determine the relationship between age, anthropometric measurements of children, and ultrasound measurements of the spleen. Reference intervals were established using non-parametric reference limits (2.5th -97.5th ) and (5th - 97th ) percentiles by MedCalc software version 20.0.3. Results Four hundred three children aged from 7 to 15 years were included in this study. The mean sonographic longitudinal (length), anteroposterior(depth) and transverse (width) dimension of the spleen was, (8.24 ± 1.26 cm), (3.98 ± 0.57 cm), and (4.26 ± 0.59 cm) respectively. The mean volume of the spleen was 75.04 ± 23.92 cm3. The height and body surface area of children were best correlated with sonographic dimensions of the spleen. Reference intervals were established using height, age, and body surface area specific for clinically practical dimensions of the spleen. Conclusions According to this study, the children are considered as having enlarged longitudinal dimension of the spleen(splenomegaly) if he or she has a size above 97.5th percentile based on their respective height.